(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2014)
There is a dialectical relationship and a close link between the rights of the Palestinian and the ground up to the degree of sanctification are any land code survival and existence, steadfastness and unity and the source of longing and nostalgia for the homeless and expatriates in the Diaspora and exile forced a gain many dimensions in Arabic literature to meet the projects uprooting and deportation and carried by Mahmoud Darwish Anon to speak out and tells it and sing its praises from the earth, longing for freedom and a fraction of the restrictions of the occupation.